Expression of stress related genes of Penaeus varnamei in biofloc closed breeding system / Nguyen Truong An - Nguyen , Truong An (2020)

(untitled)
The Pacific shrimp Penaeus vannamei, which is also known as the whiteleg shrimp, is fast becoming a key species of shrimp farming worldwide since this species has been cultured widely in many countries, such as Mexico, America, especially in Southeast Asian countries including Thailand, Vietnam, and Malaysia. In addition, the shrimp aquaculture industry has applied many new cultural techniques, especially biofloc technology – which is an eco-friendly culture technique and has many advantages over other traditional methods, such as high productivity, the stable environment of the culture, and low levels of feed conversion. Unfortunately, for so many years, shrimp farming has been constantly hounded by stress, which is caused by several factors of the culture environment including the temperature of the water, dissolved oxygen, salinity, and pH. Stress can give negative effects on cultured shrimps, such as slow growth or high mortality, subsequently economic losses. Therefore, it is important to identify whether shrimp farming using biofloc technology causes any stresses to the Pacific white shrimp. It has been investigated that when the shrimps being stressed, they can generate various physiological as well as genomic reactions to modify the mechanism of compensation or adaptation, thus allowing the mitigation of stressors as well as the maintenance of their hemostasis that help them to survive under the pressure of stress. Therefore, environmental stressors can be determined by detecting those genes associated with the stress response. In the current study, three different sets of primers were used for the amplification of catalase, Na+-K+ATPase α-subunit, and heat shock protein 70 – these are the genes that respond to hypoxia stress, salinity stress, and heat shock stress, respectively. Sequences of those primers that were used for the amplification of catalase and Na+-K+ATPase α-subunit were designed according to the published mRNA sequences of L. vannamemi available, while sequences of the primers used for amplification of heat shock protein 70 were retrieved from literature. qPCR was then applied for determining the expression of those three genes in the shrimps which were reared in four different biofloc culture conditions over a six-week period. The four conditions included microbubble aeration, a mixture of microbubble and macro bubble, macro bubble with bioballs, and macro bubble without bioballs. The up-regulated of catalase expression was found in the condition of microbubble and the condition of macro bubble with bioballs during the last two weeks of the cultivation and in the condition of macro bubble without bioballs in the 3rd, 4th, and 5th week of the cultivation. Meanwhile, the expression of Na+-K+-ATPase α-subunit was up-regulated in the condition of microbubble during the last two weeks of the cultivation, and in the condition of macro bubble with bioballs at the end of the cultivation. Lastly, the up-regulated of hsp70 was found in all four conditions throughout the cultivation. A negative correlation was found between temperature and hsp70 (n = 3; R2 = 0.454; p < 0.05). These findings make catalase, Na+-K+-ATPase α-subunit, and hsp70 genes a suitable predictive biomarker for penaeid shrimps.